PELATIHAN PEMBUATAN RENCANA PEMBANGUNAN JANGKA MENENGAH DESA (RPJMDES) DI KECAMATAN SIDOMULYO KABUPATEN LAMPUNG SELATAN - Ekana P.S, Yana; Krisbintoro, R. Sigit; Kurniawan, Robi Cahyadi; Indrajat, Himawan (Prosiding Pengabdian FISIP Unila, 2012)
The event was held at the District Office Sidomulyo South Lampung regency with two methods of activities,  lectures  and discussions  as well as practical training RPJMDesa creation. The conclusions obtained  from the  comparison of  the results of pre-test  to  post-test does not necessarily be  used as  the foundation of the legitimacy and validity of  changes in knowledge,  attitudes and  behaviors that  are expected  due to  the characteristics of  village  officials  who  attend  counseling  peemrintahan  is  very diverse.  The condition can actually be better than at the time of counseling done, or maybe even  no  better than  what comes out  of the  post-test  assessment results  in  this extension. Guidance on procedures RPJM Sidomulyo village  in the district  is the first step  to  the basic  thinking  strategic step  what needs to be  done in order  to continue  this outreach  in the  form of other  service activities. This is to complete the transformation not only of knowledge, but also attitudes and behaviors. Keywords: Rural Development, Planning and Development.